Forment, Carlos A. Democracy in Latin America. 1760-1900. Volume I, Civic Selfhood and Public Life in Mexico and Peru. Chicago and London: The University of Chicago Press, 2003, 454 pp. - Espinoza, Antonio (2006)
La reseña no presenta resumen.